On the atomic structure of thiol-protected gold nanoparticles: A combined experimental and theoretical study - Mariscal, Marcelo (2010)
In the present work new findings on the structure of the S-Au interface are presented. Theoretical calculations using a new semiempirical potential, based on density functional theory and a bond-order Morse potential, are employed to simulate the adsorption process in a more realistic way. The simulation results reveal the formation of gold adatoms on the nanoparticle surface and high surface disorder due to the strong S-Au bond. Experimental data were acquired by aberration (Cs) corrected scanning transmission electron microscopy (STEM) using a high angle annular dark field detector (HAADF) that showed a great similarity with the theory predicted.